Ordination obscures the influence of environment on plankton metacommunity structure. Issue 1 (14th November 2016) - Dallas, Tad A.; Kramer, Andrew M.; Zokan, Marcus; Drake, John M.
Abstract: The composition of plankton communities in individual habitats is often influenced by environmental conditions like pH or hydroperiod. At larger scales, environmental gradients can influence community structure across interconnected local communities. Detecting the role of environmental and spatial factors on metacommunity structure depends on the ordering of sites and species prior to analysis. We investigated this ordination in two wetland metacommunities; a well‐sampled, hyper‐diverse zooplankton metacommunity, and a Central American phytoplankton metacommunity. We calculated coherence, turnover, and boundary clumping to classify the structure of the metacommunity, and we propose a statistic that responds to variation in both coherence and turnover. Traditional ordination approaches failed to discern metacommunity structure, while significant structure existed along abiotic gradients in both zooplankton and phytoplankton systems. This shows that abiotic controls on community composition may not be detectable with traditional analyses, and suggests an alternative of ordering sites by known abiotic gradients.